Public Perception of Inheritance Distribution for Adopted Children under Islamic Law Perspective in Sungai Jawi Urban Village, West Pontianak District, Pontianak City - Rafif Athallah Dinanda; Ahmad Husaini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Child adoption is a common practice in Indonesian Muslim society, including in Sungai Jawi Urban Village, West Pontianak, yet it frequently triggers legal issues regarding inheritance distribution. This study specifically aims to analyze how the community harmonizes adoption practices with normative constraints in faraidh principles to avoid inheritance conflicts. The research employs a qualitative approach with a descriptive-analytical design through a normative-sociological perspective. Data were collected via semi-structured interviews with ten informants who have adopted children. The results reveal that although the community possesses a strong understanding regarding the status of adopted children as non-heirs, there is a collective tendency to seek legal solutions through hibah (gifts) and wasiat (wills). These findings demonstrate that such mechanisms are chosen as a middle ground to guarantee the economic rights of adopted children while ensuring that property distribution remains aligned with Sharia law. Adoption is generally practiced informally within families, driven by social, humanitarian, and kinship considerations. These findings indicate a separation between emotional bonds in upbringing and normative faraidh provisions in wealth distribution. This study contributes to strengthening the understanding of how society negotiates Islamic legal norms with social realities, affirming hibah and wasiat as adaptive instruments in maintaining a balance between legal and social justice.